DAMPAK RELOKASI PASAR TRADISIONAL TERHADAP PENDAPATAN PEDAGANG (STUDI KASUS DI PASAR RAKYAT TALANG BANJAR KECAMATAN JAMBI TIMUR) - Milen Eva Pertiwi; Titin Agustin Nengsih; Yuliana Safitri (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine the impact of market relocation on the income of traders in the Talang Banjar People's Market, the factors that affect the income of traders after being relocated and how traders perceive the market relocation. In this study using qualitative research methods. As for the type and source of data needed, namely primary and secondary data. Data collection techniques are carried out by observing, interviewing and documenting while data analysis methods include data reduction, data presentation and drawing conclusions or verification. The results of the study showed that the income of traders after being relocated experienced a change in income where out of the 40 traders who had been interviewed, 38 traders had a decrease in income while as many as 2 traders had an increase in income. As for the factors that affect traders' income, namely location factors, trading hours, mods and competition. the perception of traders regarding the relocation of the Talang Banjar People's Market is not as expected, mainly because the number of traders' income has decreased. So it is hoped that government traders can make improvements to bring changes in a better direction, namely by repairing the market building, expanding road access, expanding stalls and kiosks according to the needs of traders and traders hope that all traders will be included in the market building.